DAMPAK PEMBELAJARAN DARING TERHADAP PSIKOLOGI SISWA SMA/SMK SEBAGAI EFEK PANDEMI COVID-19 DI LINGKUNGAN KARANG BUAYA PAGUTAN TIMUR: IMPACT OF ONLINE LEARNING ON LEARNING PSYCHOLOGY OF SMA/SMK STUDENTS AS THE EFFECT OF THE COVID-19 PANDEMIC IN THE LINGKUNGAN KARANG BUAYA OF EAST PAGUTAN - Lailan khairiawati; Raehanah Raehanah; Sulistiyana Sulistiyana (UIN Mataram, 2021)
With the implementation of online learning due to COVID-19 by the Indonesian government, it has greatly impacted the psychology of student learning, especially high school/vocational students. The Karang Buaya neighborhood of Mataram City is one of the areas where high school/vocational high school students learn to use online learning. The environment is one of the factors that can affect student learning, because students are less able to control themselves to focus on online learning. Learning through the internet is a new thing for students because the quota to access the internet and the network is less stable. This certainly interferes with the effectiveness of learning, slowness of thinking, weakened immunity, boredom and lack of social interaction. The purpose of this research is to find out the form of online learning, learning psychology symptoms and how high school/vocational high school students cope with learning psychology symptoms. Sources of data obtained from interviews with high school/vocational students who use online learning. The research approach used is descriptive qualitative. Collecting data by observation, interviews and documentation. The results showed that online learning was not effective for students because it had an impact on student learning psychology. However, with this, students can overcome the way of learning with their own will so that high school / vocational students are more comfortable in learning. Pembelajaran daring selama pandemic COVID-19 memberikan dampak psikologis bagi siswa termasuk siswa SMA/SMK. Lingkungan Karang Buaya Kota Mataram menjadi salah satu daerah yang mempunyai siswa-siswi SMA/SMK yang belajar menggunakan pembelajaran online. Lingkungan menjadi salah satu faktor yang dapat mempengaruhi belajar siswa, karena siswa kurang mampu mengendalikan diri untuk fokus dalam belajar daring. Belajar melalui jaringan internet menjadi hal baru yang dilakukan siswa karena kuota untuk mengakses internet dan jaringan kurang stabil. Hal ini tentu mengganggu keefektifan belajar, kelambanan berfikir, kekebalan tubuh melemah, bosan dan kurangnya interaksi sosial. Tujuan peneilitian ini adalah untuk mengetahui bentuk pembelajaran daring, gejala psikologi belajar dan cara siswa SMA/SMK mengatasi gejala psikologi belajar. Sumber data diperoleh dari wawancara dengan siswa SMA/SMK yang menggunakan pembelajaran daring. Pendekatan penelitian yang digunakan adalah kualitatif deskriptif. Pengumpulan data dengan observasi, wawancara dan dokumentasi. Pembelajaran daring tidak efektif bagi siswa karena berdampak terhadap psikologi belajar siswa. Namun dengan hal itu siswa dapat mengatasi cara belajar dengan kehendak masing-masing agar siswa SMA/SMK lebih nyaman dalam belajar.